KEY BUSINESS PRIORITIES AND GOOD PRACTICES OF INDUSTRIAL MANAGEMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The topicality of the issue under consideration is determined by the need to outline the directions of development of industrial management as a result of the changes that have occurred in a national and global aspect. Good practices for introduction, dissemination and promotion in modern business organizations are presented with the possible approaches and tools for achieving more effective results and sustainable development. They will help employers and top managers to attract and retain the necessary highly qualified specialists in key professions.